Success criteria of SMMEs for - Sutherland, Scott (My University, 2011)
Many SMME in South Africa have attempted to enter exporting, often with very bad experiences and losses. This is not consistent with the experiences of similar small firms in first world countries. Given that South African SMME may find great difficult competing in first world markets without prior exporting experience. This research seeks to fill a gap in the literature by looking if there are issues that may be particular to South African firms looking to export in Africa. In particular what could be the key criteria small firms lacking in finances and management resources can concentrate upon to try ensure success? The researcher was seeking a wide view of the exporting industry and sought out a group of experts to gain insight to the possible key success criteria. A phenomenological approach using an unstructured interview was done with these experts to gain insight of both successful and unsuccessful export ventures. In particular what these experts have advised smaller firms on and where the firms have succeeded. There was convergence from the respondents that the networks or relationships of an exporting SMME are of key importance. This is largely due to the nature of complexities of exporting and the diversity of requirements in multiple jurisdictions. As there can be no certainty all problems have been provided for by the exporter working alone, the exporter and importer are dependent upon each other and their business partners to ensure mutually beneficial transactions
MBA - WBS
Keywords: Small businesses; Medium sized businesses; Micro businesses; Exports